(untitled) (World Economics and Finance Bulletin, 2024)
Modern business and technological changes on the business and operations of the enterprise and the industry plays a decisive role in the formation of strategies. Environmental problems such as climate change and scarcity of resources in this article, the dynamic between technology and the business impact of correlation taraqqiylashayotgan learn. Case studies and scientific literature through the study of adaptation to technological innovation by enterprises and the environmental pressure is aimed at covering the use of strategies for sustainable growth.